A synthetic cervix model and the impact of softness on cerclage integrity. Issue 5 (6th October 2019) - Baumer, Alexa; Gimovsky, Alexis C.; Gallagher, Michael; Leftwich, Megan C.
Abstract : Cervical insufficiency is a medical condition of pregnancy which causes the cervix to soften, shorten and dilate before full term, typically between 18 and 22 weeks of gestation, such that a preterm birth occurs. It is a common cause of second trimester pregnancy loss. Before meeting the diagnostic criteria, a patient that experiences early cervical remodelling or the development of a short cervix may receive surgical intervention. Once detected, the typical treatment is a cerclage procedure (a purse string suture to close the cervix) and progesterone medication. There are conflicting studies on the efficacy of the cerclage procedure, with conclusions drawn from clinical evidence as opposed to mechanical properties. The purpose of this study is to understand the mechanical limitations of the cerclage procedure. Working with physicians at George Washington University School of Medicine and Health Sciences, we created generalized three dimensional models of the cervix from ultrasound images. To fabricate the synthetic cervices, we used a silicone rubber to mimic the qualitative feel of the cervix according to collaborating physicians. Using this qualitative information, we performed material testing for quantitative analysis. The synthetic cervices were then sutured using clinical techniques. The maximum force required for the synthetic tissue to rupture due to the cerclage stitch was recorded. The impact of material softness on the integrity of the cerclage is investigated.